Measurement of Υ production in pp collisions at √s = 5 TeV - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kubat, Jakub; Leverington, Blake; Marks, Jörg; et al. (Journal of high energy physics, 2023)
The production cross-sections of Υ mesons, namely Υ(1S), Υ(2S) and Υ(3S), in pp collisions at √s = 5 TeV are measured with a data sample corresponding to an integrated luminosity of 9.13 ± 0.18 pb−1 collected by the LHCb detector.